2021
DOI: 10.3390/ijerph18168248
|View full text |Cite
|
Sign up to set email alerts
|

Association of Healthy Diet with Recovery Time from COVID-19: Results from a Nationwide Cross-Sectional Study

Abstract: The world is still in need of an effective therapy to treat coronavirus disease-19 (COVID-19). This cross-sectional study was conducted on COVID-19 survivors in Saudi Arabia to investigate the influence of a healthy diet on the recovery time from COVID-19. A questionnaire was developed to assess participants’ dietary habits, based on the 2015 Dutch food-based dietary guidelines. A total of 738 COVID-19 survivors participated in the study, of whom 237 (32.1%) were hospitalized for COVID-19 treatment while 501 (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 74 publications
(96 reference statements)
1
4
0
Order By: Relevance
“…However, no significant association was found between the traditional dietary pattern and convalescence duration in patients with COVID-19. In line with our findings, a cross-sectional study on COVID-19 survivors in Saudi Arabia indicated that more adherence to a healthy diet was associated with a shorter duration of recovery from COVID-19 ( 16 ). Further studies about different common known dietary patterns are needed to expand the current finding.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, no significant association was found between the traditional dietary pattern and convalescence duration in patients with COVID-19. In line with our findings, a cross-sectional study on COVID-19 survivors in Saudi Arabia indicated that more adherence to a healthy diet was associated with a shorter duration of recovery from COVID-19 ( 16 ). Further studies about different common known dietary patterns are needed to expand the current finding.…”
Section: Discussionsupporting
confidence: 91%
“…Another study about COVID-19 symptoms and habitual food intake in adult outpatients indicated that an increase in habitual intake of legumes and grains, bread, and cereals was associated with reduced overall symptom severity in patients with COVID-19 ( 11 ). A recent study about diet and duration of recovery from COVID-19 showed that adherence to a healthy diet was associated with a shorter duration of recovery from COVID-19 ( 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…Society and culture Abduljawad [147]; Abolfotouh et al [148]; Abouzid et al [96]; Abu Hatab et al [99]; Ahmed [86]; Aijehany and Allily [149]; Al Agha et al [60]; Al Kassaa et al [87]; Al-Abdi et al [143]; Alafif et al [151]; Alah et al [144]; Alamri et al [152]; Alazaiza et al [140]; AlBlooshi et al [188]; Aldhwayan and Alabdulkader [153]; Alfayez et al [61]; Alghadir et al [62];…”
Section: Sustainability Dimension * Documents Topics Addressedmentioning
confidence: 99%
“…Abduljawad [147]; Abolfotouh et al [148]; Aijehany and Allily [149]; Al Agha et al [60]; Al Sadig et al [150]; Alafif et al [151]; Alamri et al [152]; Aldhwayan and Alabdulkader [153];…”
mentioning
confidence: 99%
See 1 more Smart Citation